Real time diagnosis of environmental stress by micromorphometric method, 1: Effect of air temperature during fruitlet stage of fruit on stem and fruit diameters, and fruit growth in Japanese pear tree (Pyrus serotina Reheder cv. Kosui) - Ito, J. (Hiroshima-ken. Agricultural Experiment Station, Higashihiroshima (Japan)); Hasegawa, S; Fujita, K; Ogasawara, S; Fujiwara, T (Soil science and plant nutrition (Tokyo), 1999)
The effects of air temperature during the fruitlet stage on stem and fruit diameters, and fruit production were examined in Japanese pear trees (Pyrus serotina cv. Kosui). Under controlled environmental conditions, plants at the fruitlet stage of fruit were exposed to three different air temperature regimes; 16, 23, and 30 degrees C for 2 d. Under glasshouse conditions, they were exposed to two night air temperature regimes: 11 and 18 degrees C for 35 consecutive days during the initiation and fruitlet stages of fruits. Changes in the stem and fruit diameters during the treatment and/or residual effect were analyzed by the micromorphometric technique. Fruit growth increased most at 23 degrees C, followed by 30 degrees C and least at 16 degrees C during the 2 d-period under the controlled environment. Under a lower temperature regime (16 degrees C), fruit growth decreased a few hours after "lights on" in the morning while under a higher one (30 degrees C), fruit growth slowed down about 24 h after treatment initiation. The stem diameter decreased in the daytime and recovered at night and the decrease in the daytime was less pronounced under the lower than the higher temperature regime. Similar effect of night air temperature regimes on the changes in the fruit and stem diameters was observed in plants grown under glasshouse conditions. Residual effect was observed during the fruitlet stage, but disappeared during maturation. The average weight of the mature fruit was greater under a higher than a lower temperature regime while no significant effect was observed on the fruit quality including total sugar concentration, acidity, and hardness. Based on the current data, we conclude that the effect of the air temperature on fruit growth could be diagnosed in real time (less than 24 h) by monitoring the changes in the fruit and stem diameters using a stain gaugetype microdisplacement detector